Quantum theory from first principles : an informational approach - D'Ariano, G. M. (Giacomo M.); Chiribella, Giulio; Perinotti, Paolo (Cambridge University Press, 2019)
"Quantum theory is the soul of theoretical physics. It is not just a theory of specific physical systems, but rather a new framework with universal applicability. This book shows how we can reconstruct the theory from six information-theoretical principles, by rebuilding the quantum rules from the bottom up. Step by step, the reader will learn how to master the counterintuitive aspects of the quantum world, and how to efficiently reconstruct quantum information protocols from first principles. Using intuitive graphical notation to represent equations, and with shorter and more efficient derivations, the theory can be understood and assimilated with exceptional ease. Offering a radically new perspective on the field, the book contains an efficient course of quantum theory and quantum information for undergraduates. The book is aimed at researchers, professionals, students in physics, computer science and philosophy, as well as the curious outsider seeking a deeper understanding of the theory"--